2021
DOI: 10.1002/ana.26071
|View full text |Cite
|
Sign up to set email alerts
|

NIA‐AA Alzheimer's Disease Framework: Clinical Characterization of Stages

Abstract: Background To operationalize the National Institute on Aging – Alzheimer's Association (NIA‐AA) Research Framework for Alzheimer's Disease 6‐stage continuum of clinical progression for persons with abnormal amyloid. Methods The Mayo Clinic Study of Aging is a population‐based longitudinal study of aging and cognitive impairment in Olmsted County, Minnesota. We evaluated persons without dementia having 3 consecutive clinical visits. Measures for cross‐sectional categories included objective cognitive impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Pearson's correlations were used to assess the association between 3-month slopes on the C3 and change on the PACC5 over 1 year. We then conducted Receiver Operating Characteristic (ROC) analyses to quantify how accurately C3 slopes could identify individuals who would show more than 0.10 SD decline on the PACC5 over 1 year, which has previously been suggested as a clinically meaningful cut-off for annual decline in amyloid positive cognitively normal individuals (Papp et al, 2020 ; Petersen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson's correlations were used to assess the association between 3-month slopes on the C3 and change on the PACC5 over 1 year. We then conducted Receiver Operating Characteristic (ROC) analyses to quantify how accurately C3 slopes could identify individuals who would show more than 0.10 SD decline on the PACC5 over 1 year, which has previously been suggested as a clinically meaningful cut-off for annual decline in amyloid positive cognitively normal individuals (Papp et al, 2020 ; Petersen et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Upon seeing improvement, we investigated whether PE on computerized testing could be observed over the first 3 months, as we expected that the PE signal would be strongest over the first 4–5 assessments (Watson et al, 1994 ; Calamia et al, 2012 ; Samaroo et al, 2020 ). Next, we examined the relationship of individual variation in shorter term PE (i.e., 3 months) with (1) AD biomarker burden measured using neuroimaging and (2) cognitive decline on standard paper-pencil cognitive testing over 1 year (Petersen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, from the two studies that did include younger adult individuals (age ≥ 30), both found significant associations between MeDi and structural (specifically WMI) and functional neuroimaging markers (specifically Aβ and glucose metabolism) ( 34 , 39 ). It has been suggested that the earliest pathological changes may be detected using neuroimaging markers between 15 and 30 years preceding symptom onset ( 42 , 73 , 74 ). As most studies captured older-aged individuals, it is difficult to understand how long an individual must have adhered to a DP, to influence changes in brain ageing.…”
Section: Discussionmentioning
confidence: 99%
“…74 However, the true application of these new research-based criteria needs validation and is likely to undergo further revisions. 75 Positron Emission Tomography-based Biomarkers Currently four tracers for Aβ plaques and neurofibrillary tau have been approved by the US Food and Drug Administration (FDA). For both Aβ and tau pathologies, postmortem studies have demonstrated a strong regional correlation between premortem PET scans and postmortem pathology.…”
Section: Pathology-related Biomarkersmentioning
confidence: 99%